Cardiovascular risk factor reporting in immune checkpoint inhibitor trials: A systematic review. (April 2023) - Tan, Sean; Sivakumar, Seiyon; Segelov, Eva; Nicholls, Stephen J.; Nelson, Adam J.
Abstract: Background: Immune checkpoint inhibitors (ICI) have revolutionized the treatment of numerous cancers but are associated with increased risk of myocardial infarction. The prevalence of traditional cardiovascular risk factors (CVRF) in patients treated with ICIs is unknown. This study sought to describe the frequency of reporting of CVRFs among landmark ICI trials. Methods: A systematic review of all phase 2 or 3 cancer trials employing ICIs that led to United States Food and Drug Administration approval was conducted. Results: Of the 69 identified trials, only one study reported baseline rates of hypertension, diabetes mellitus, and dyslipidemia. Smoking history was reported in 27 studies (39 %) and three (4 %) reported body mass index. No study reported history of previous cardiovascular disease, although 17 (25 %), six (9 %), and 21 (30 %) studies excluded patients with recent myocardial infarction, revascularization and heart failure respectively. Similarly low rates of cardiovascular risk factor reporting were observed in studies employing concurrent vascular endothelial growth factor inhibitors and recruiting (neo)adjuvant cohorts. Conclusion: The prevalence of CVRFs is poorly described in ICI trials despite increasingly reported risks of myocardial infarction. A systematic approach to collecting and reporting CVRFs should be considered in future trials and real world populations. Graphical Abstract: Reporting of cardiovascular risk factors in immune checkpoint inhibitor trials. Cardiovascular risk factors are poorly defined in landmark immune checkpoint inhibitor trials. Each trial included in the systematic review is represented in the figure by their trial name (CM – CheckMate trial, KN – KEYNOTE trial). Trials with cardiac exclusion factors are listed on right of the dotted line. Trials that reported prevalence of smoking are depicted in the red bubble, BMI in the blue bubble, and hypertension, dyslipidemia and diabetes in the yellow bubble. Only one trial reported all conventional cardiovascular risk factors at baseline (overlap of red, blue and yellow bubbles). Trials that did not report any cardiovascular risk factors are depicted outside the coloured bubbles. Trials which utilized concurrent cardiotoxic vascular endothelial growth factor inhibitors are highlighted in red font. A complete list of the included trials are available in the Supplementary appendix . *Adjuvant trials. **Neoadjuvant trials . BMI – Body mass index, CM – CheckMate, KN – KEYNOTE . ga1 Highlights: Immune checkpoint inhibitors (ICI) are associated with myocardial infarction (MI). Cancer and MI share risk factors such as smoking, diabetes and obesity. Cardiovascular risk factors (CVRF) are rarely reported in seminal ICI trials. Future trials should consider CVRF reporting to guide cardiovascular risk reduction.